2008
DOI: 10.1159/000149811
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle and Liver Oxidative Metabolism in Response to a Voluntary Isocaloric Intake of a High Fat Diet in Male and Female Rats

Abstract: High fat diets (HFD) usually lead to hyperphagia and body weight gain. However, macronutrient proportions in the diet can modulate energy intake and body fat deposition. The aim of the study was to investigate muscle and liver oxidative metabolism in response to an isocaloric intake of a HFD and to elucidate the possible gender-dependent response. Eight week-old male and female rats were fed either standard chow or HFD for 14 weeks. Energy intake, body weight and whole animal oxygen consumption were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 50 publications
9
33
0
2
Order By: Relevance
“…As skeletal muscle from female rats exhibits greater mitochondrial mass, antioxidant protection, and oxidative-phosphorylative capacities than that from males (Colom et al 2007a, Català-Niell et al 2008, Gó mez-Pérez et al 2008, and E 2 has been shown to play a role in mitochondrial modulation in other tissues (Mattson et al 1997, Chen et al 1999, Rodríguez-Cuenca et al 2007, Moreira et al 2011, Nadal-Casellas et al 2011b, Amengual-Cladera et al 2012a, the aim of the present study was to elucidate the role of sex hormones in these differences, as well as their relationship with adiponectin production in skeletal muscle. This was accomplished by using a model of ovariectomized (OVX) rats to test the effects of a decrease in ovarian hormone levels and of E 2 replacement, combined with in vitro experiments with L6E9 myotubes, which were treated with E 2 , progesterone (Pg), and testosterone.…”
Section: Introductionmentioning
confidence: 87%
“…As skeletal muscle from female rats exhibits greater mitochondrial mass, antioxidant protection, and oxidative-phosphorylative capacities than that from males (Colom et al 2007a, Català-Niell et al 2008, Gó mez-Pérez et al 2008, and E 2 has been shown to play a role in mitochondrial modulation in other tissues (Mattson et al 1997, Chen et al 1999, Rodríguez-Cuenca et al 2007, Moreira et al 2011, Nadal-Casellas et al 2011b, Amengual-Cladera et al 2012a, the aim of the present study was to elucidate the role of sex hormones in these differences, as well as their relationship with adiponectin production in skeletal muscle. This was accomplished by using a model of ovariectomized (OVX) rats to test the effects of a decrease in ovarian hormone levels and of E 2 replacement, combined with in vitro experiments with L6E9 myotubes, which were treated with E 2 , progesterone (Pg), and testosterone.…”
Section: Introductionmentioning
confidence: 87%
“…In accordance with our findings, other authors have reported higher oxidative capacity in the gastrocnemius muscle of female Wistar rats. Català-Niell et al [12] demonstrated higher mitochondrial respiration at state 4 and state 3. Colom et al [10] found higher enzymatic activities for some electron transport chain complexes in the mitochondria of females compared with males.…”
Section: Effects Of Gender In Sedentary Ratsmentioning
confidence: 95%
“…Redox status also shows gender differences, as female rats often suffer less oxidative damage than males. Català-Niell et al [12] reported that muscle mitochondria from females produce significantly less hydrogen peroxide and have more effective antioxidant capacities than those from males.…”
Section: Effects Of Gender In Sedentary Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three employed the mouse as an animal model (1, 3-5, 11, 15-17, 25, 32, 33, 40, 44, 49, 52, 53, 57, 63, 67, 74, 75, 78, 79), 16 employed the rat (6,23,35,38,42,43,48,58,70,71,73,77,80,82,84,85) and one used the Brandt's vole (86) and the house shrew (69), respectively. Whenever possible, we compared both the regulatory effect of a given parameter across different studies and within the same study.…”
Section: Ucp1 In Brown Adipose Tissuementioning
confidence: 99%